Prospektif Identifikasi Kejadian Medication Error pada Tahap Inventory High Alert Medication di Gudang Farmasi Induk RSUP Fatmawati Periode November 2025 - Shania Felisia (Jurnal Farmasi Klinik Best Practice, 2025)
The management of high-alert medications requires special attention due to their high risk of causing patient harm when errors occur. This study aims to identify deviations in the storage and distribution of high-alert medications at the Central Pharmacy Warehouse of Fatmawati Central General Hospital and to assess their compliance with the standards of the Ministry of Health (2019) and ISMP (2018). The method used was direct observation during November 2025. A total of 50 deviations were found, consisting of 26 cases related to labeling (76.5%) and 8 cases related to storage (23.5%). The most common deviations included the absence of “High Alert” labels, discrepancies in stock cards, and improper arrangement of medications according to risk categories. Based on the NCC MERP adaptation, all findings were classified as potential errors without immediate clinical impact but with the possibility of leading to medication errors. These results indicate that the labeling and monitoring system for high-alert medications at Fatmawati Central General Hospital has not been optimal, necessitating improvements through consistent labeling, separation of storage areas, and strengthened stock monitoring.